Factors Associated with The Incidence of Acute Respiratory Infections in Toddlers - Hairat, Ummul (GLOBAL HEALTH SCIENCE GROUP, 2024)
Acute Respiratory Infection (ARI) is the biggest death disease in babies and toddlers, especially in developing countries where one toddler dies in 20 seconds or 3 people per minute. This research aims to find out what factors are associated with the incidence of ARI in toddlers at the Antang Makassar Community Health Center. This research is a type of analytical observational research using the Cross Sectional Study method. The sampling technique used accidental sampling and count of sample is 44 respondents was obtained in accordance with the inclusion criteria. Data collection was carried out using questionnaire measuring instruments which has been modified and taken from several previous research results that have been validated and observation sheets. The results of this study showed that the percentage of ARI incidents in toddlers was 93.2% and the p.value for immunization status with ARI incidents was 0.006, p.value house environmental with ARI incidents was 0.003, and p.value mother’s knowledge with ARI incidents was 0.002. The conclusion of this research is that there is a correlation between immunization status, house environmental, and mother’s knowledge with the incidence of ARI in toddlers.